The Bride of the Nile $1 (BVolume 05s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bride of the Nile $1 (BVolume 05" by Georg Ebers is a historical novel likely written in the late 19th century. The story unfolds against the backdrop of ancient Egypt, focusing on themes of love, loss, and redemption as it navigates through the complex relationships among its characters, particularly centering on Orion, a troubled soul grappling with his father's death and the consequences of his actions. At the start of the novel, we are introduced to Orion, who is engulfed in his grief after his father's death and struggling with feelings of guilt and despair. His emotional turmoil is palpable as he reflects on his perceived failures and the impact of his father's curse on his life. Amidst his solitude, little Mary enters the scene, offering a poignant reminder of innocence and the need for forgiveness. Their interaction reveals deep layers of complexity in their relationship, hinting at themes of childhood innocence, culpability, and love. As Orion wrestles with his pain, the narrative sets the stage for unresolved tensions and the potential for reconciliation, establishing emotional stakes that resonate throughout the novel. The opening portion effectively draws readers into a world of emotional depth, suggesting that the journey ahead will explore themes of absolution and the quest for redemption. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: German fiction -- Translations into English; Egypt -- History -- Fiction